Evaluating the barriers to point-of-care documentation for nursing staff. - Kohle-Ersher, Angela; Chatterjee, Pooja; Osmanbeyoglu, Hatice Ulku; Hochheiser, Harry; Bartos, Christa (CIN: Computers, Informatics, Nursing, 2012)
Point-of-care documentation has been identified as a patient safety measure for improving accuracy and timeliness of data. To evaluate the barriers that nurses and nurse aide/clinical technicians encounter for electronic point-of-care documentation, we conducted surveys on a telemetry unit at a southwestern Pennsylvania community hospital. Our first survey revealed that the location of the in-room computers, perceived lack of in-room computer reliability, Health Insurance Portability and Accountability Act/privacy concerns, and perceptions of the patients' response to charting on computers in patient rooms were all barriers to point-of-care documentation. Our second survey revealed that workflow priority issues were also a barrier to point-of-care documentation, as staff members did not rate documentation as a high priority in terms of delivering timely medical care. Changes in both nursing practices and hospital infrastructure may be needed if these barriers to point-of-care documentation are to be overcome.